Teachers’ Perception about Information and Communication Technology - Lamichhane, Purna Bahadur (Patan Pragya, 2022)
This research article is an attempt to identify the perception of teachers towards Information communication technology (ICT) in classroom teaching. A survey research design was used to carry out the research. Using the opportunity sampling procedure, the perception of thirty English teachers teaching at ten selected community schools in Gorkha district were taken as samples. A questionnaire was used to collect the data. After analyzing the data, it was found that the ability to operate, use, assess, communicate, organize, transfer, download, and create modern data is referred to as computerized competency. These talents are critical for both students and instructors in the development of e-learning. Teachers' favorable digital education aptitudes have a big impact in teaching and learning when all of these factors are considered.